Change in Columellar–Philtral and Nasolabial Angles Over Time Following Rhinoplasty - Brennan, Tara E.; Trujillo, Oscar; Sina, Mehdi; Vandenberg, Katherine N.; Myers, Orrin; Pearlman, Steven J. (Facial Plastic Surgery, 2022)
Preoperative analyses of the columellar–philtral and nasolabial angles (CPA and NLA) are important considerations for the rhinoplasty surgeon. This study aims to quantify and compare the degree of change in nasal tip rotation as measured by CPA and NLA over time following rhinoplasty and to identify surgical maneuvers or patient characteristics that may affect nasal tip rotation. Prospective analysis of CPA and NLA in 111 consecutive, consenting cosmetic, and/or functional rhinoplasty patients of the senior author over a 1-year time period was performed. Angles were analyzed before surgery, immediately after surgery, and at 1 week, 1 month, 6 months, and 1 year following surgery. Subgroup analyses based on surgical maneuvers and other covariates were performed. The greatest change to CPA and NLA in the upright position was 11.8 degrees (95% confidence interval [CI]: 9.8–13.7, p < 0.001) and 9.3 degrees (95% CI: 7.9–10.7, p < 0.001) of elevation 1 week after surgery, respectively. The mean CPA was not significantly different than preoperative measures 6 months after surgery; however, the NLA remained 4.94 degrees (95% CI: 2.1–8.4, p = 0.001) elevated. Females showed approximately 10 degrees more elevated CPA than males in pre- and postoperative time points; however, the NLA did not discriminate between sexes. Transfixion incisions appears to cause a significant decrease in postoperative NLA compared with patient who did not undergo transfixion incisions. Measurements for nasal tip rotation are variable and inconsistent throughout the literature. This study shows that rhinoplasty may have a greater effect on nasal tip rotation as measured by NLA and that the effects of NLA and CPA are independent, signifying that a standardized measurement for nasal tip rotation is warranted.
Keywords: nasolabial angle; rhinoplasty; columellar–philtral angle